On the short and long term real effects of nominal exchange rates - Yunus Aksoy; Hanno Lustig (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
In this paper we assess the implications of sunk costs and product differentiation on the pricing decisions of the multinational firms. For this purpose we use a modified version of Salop's spatial competition. The model yields clear-cut predictions regarding the effects of exchange rate shocks on the market structure and on pass-through. The main results are following: shocks within the band of inaction do not affect market structure. The upper bound of this range rises as the industry ratio of sunk- to fixed costs increases. As fixed costs and product heterogeneity jointly increase, the lower bound drops. Outside of the range, depreciations cause one or several of those foreign brands closest to the home brand to leave. This decreases the overall responsiveness of prices to exchange rate shocks. Large appreciations induce entry and increase the elasticity of prices. This asymmetry implies larger positive than negative PPP deviations. When accounting for price changes in foreign markets, strategic pricing behaviour is no longer sufficient to generate real exchange rate variability. Incomplete pass-through obtains if and only if the domestic firms have a smaller market share abroad. With large nominal exchange rate shocks a hysteresis result obtains if and only if sunk costs are non-zero.
urn:nbn:de:hebis:30-10029
Keywords: C33; E31; 330; Market Structure; Exchange Rates; Hysteresis